2000
DOI: 10.1093/clinchem/46.6.822
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Increases in Plasma Phosphatidylcholine Hydroperoxide Concentrations in Control Subjects and Patients with Hyperlipidemia

Abstract: Background: The basal lipid peroxide concentration in the plasma of patients with hyperlipidemia may be related to atherosclerosis. Quantitative determination of lipid peroxides in the plasma is an important step in the overall evaluation of the biochemical processes leading to oxidative injury. Unfortunately, the currently available methods for lipid peroxidation lack specificity and sensitivity. Methods: Hyperlipidemic patients (44 males and 50 females), ages 12–82 years (mean ± SE, 53 ± 2.3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…Radical-mediated lipid peroxidation plays a central role in the pathophysiology of human disease. 1,2 In a previous paper, we confirmed that synthetic Amadoriglycated phosphatidylethanolamine (Amadori-PE) induces lipid peroxidation via reactive oxygen species generation in the presence of transition metals. 3 Therefore, we hypothesized that glycation of membrane aminophospholipids should be one of the critical risk factors on membrane lipid peroxidation in vivo and thus have put our efforts into the analysis of Amadori-PE in various samples.…”
Section: Introductionsupporting
confidence: 55%
“…Radical-mediated lipid peroxidation plays a central role in the pathophysiology of human disease. 1,2 In a previous paper, we confirmed that synthetic Amadoriglycated phosphatidylethanolamine (Amadori-PE) induces lipid peroxidation via reactive oxygen species generation in the presence of transition metals. 3 Therefore, we hypothesized that glycation of membrane aminophospholipids should be one of the critical risk factors on membrane lipid peroxidation in vivo and thus have put our efforts into the analysis of Amadori-PE in various samples.…”
Section: Introductionsupporting
confidence: 55%
“…Non-smokers had significant decreases in 8-isoprostane but there were great differences between individuals. PCOOH is associated with core lipid oxidation and reflects in vivo oxidative damage to organs [11]. CoQ 10 H 2 is the first antioxidant when lipoproteins are exposed to free radicals [12].…”
Section: Discussionmentioning
confidence: 99%
“…In studies of lipid peroxidation during aging, most investigations have measured poorly specific markers. However, recent studies using highly specific high performance liquid chromatography techniques have shown that membrane phospholipid hydroperoxides increase with donor age in red blood cells and plasma of healthy human subjects (Miyazawa et al, 1996;Kinoshita et al, 2000) and in rodent tissues (Tahara, Matsuo & Kaneko, 2001).…”
Section: Variations In Oxidative Damage During Agingmentioning
confidence: 99%